Celebrity Endorsement in Japan Tourism based on Consumer Celebrity Worship - Adestya Ayu Armielia (Ultima Management : Jurnal Ilmu Manajemen, 2018)
Abstract 85% commercials in Japan are promoted with celebrity endorsers, and that trend seems phenomenal knowing other Asian countries start to imitate Japan’s marketing path. One of the most influential celebrity in Japan today is Arashi, a band formed 20 years ago, who grows mature along with their solid fan base throughout the nation and outside the country. In the tight business competition, both in entertainment and tourism industry, Arashi gives fresh air to Japan economic. This study is aimed at examining the effects of the celebrity endorsement, which consist of three dimensions, and consumer celebrity worship, which consist of two dimensions, to the purchase intention with destination image as the intervening. This is a descriptive study, with approximately 18.000 of Arashi’s foreign fans in an online community; livejournal, as the population. The samples, which was taken based on Slovin’s formula, are 206 people by using non probability sampling method and purposive sampling. The technique of collecting data is online questionnaires. The validity that is used is Pearson product-moment correlation coefficient. The reliability of this study is using Cronbach Alpha; meanwhile, to measure the model, SEM with path analysis is used. Further, Moderating Regression is used to measure the moderating variables used in this study. From this study, it is concluded that the Consumer-Celebrity Worship will positively affect the Destination Image, Destination Image will positively affect Purchase Intention, Celebrity Endorsement will positively affect the Purchase Intention, Socio-demographic & economic will strengthen the link of Consumer-Celebrity Worship and Destination Image, Socio-demographic &economic will strengthen the link of Consumer-Celebrity Worship and Purchase Intention. Keywords: Celebrity Endorsement, Purchase Intention, Consumer-Celebrity Worship